Phylogenetic data reveal a surprising origin of Euphorbia orphanidis (Euphorbiaceae) and environmental modeling suggests that microtopology limits its distribution to small patches in Mt. Parnassus (Greece) - Faltner, Felix; Wessely, Johannes; Frajman, Božo (Frontiers in Plant Science, 2023)
The Mediterranean Basin is one of the most biodiverse areas in the world, harbouring 25,000 plant species of which 60% are endemic. Some of them have narrow distributions, such as Euphorbia orphanidis, which is only known from alpine screes on Mt. Parnassos in Greece. Its exact distribution in this mountain was, however, poorly known, and also its phylogenetic origin was unclear. We performed extensive field work in Mt. Parnassos and could register E. orphanidis only in five patches of limestone screes in the eastern part of this mountain range, emphasising its very narrow distribution, which is likely limited by topography influencing water availability, as indicated by environmental modelling. We also registered 31 accompanying species and thus characterised its habitat. Using nuclear ribosomal internal transcribed spacer (ITS), and plastid ndhF and trnT–trnF sequences we show that it belongs to E. sect. Patellares, despite not having connate raylet leaves typical for this section, and not to E. sect. Pithyusa as previously suggested. The relationships among the species of E. sect. Patellares are poorly resolved, suggesting their simultaneous divergence dated to the late Pliocene, which coincided with the establishment of the Mediterranean climate. The relative genome size of E. orphanidis is in the range of other members of E. sect. Patellares, suggesting that it is diploid. Finally, we performed multivariate morphological analyses to generate a comprehensive description of E. orphanidis. Based on its narrow distribution and anticipated negative impact of global warming, we consider this species endangered (EN). Our study demonstrates how microrelief can limit the distribution of plants in a topographically heterogeneous mountain environments and likely played an important, yet neglected, role in shaping distribution patterns of plants in the Mediterranean Basin.